2013
DOI: 10.1016/j.yebeh.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception of stigma in persons with epilepsy in Tehran, Iran

Abstract: Epilepsy is one of the most stigmatizing medical conditions worldwide. It could be argued that the problem of stigma and discrimination might be different in an Islamic culture. A cross-sectional study of 130 patients with epilepsy was performed using the Internalized Stigma of Mental Illness (ISMI) questionnaire that was adapted for epilepsy. The questionnaire contained 29 items on a 4-point scale in addition to an open-ended question about experience of discrimination. An average score above the midpoint (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 13 publications
1
18
2
Order By: Relevance
“…The respondents of the present study also reported supernatural origins as the cause of epilepsy, but this is much lower than other studies and this is a positive finding of our study [20, 29, 30]. In Iran few studies about knowledge of epilepsy in different population groups including teachers, people with epilepsy, general public, and relatives were conducted [4, 19, 3133]. These studies have shown different results.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The respondents of the present study also reported supernatural origins as the cause of epilepsy, but this is much lower than other studies and this is a positive finding of our study [20, 29, 30]. In Iran few studies about knowledge of epilepsy in different population groups including teachers, people with epilepsy, general public, and relatives were conducted [4, 19, 3133]. These studies have shown different results.…”
Section: Discussioncontrasting
confidence: 57%
“…A previous study in Iran found that knowledge about epilepsy of family members of patients was poor and relatives lacked information about the disease [19]. Also survey on stigma and discrimination experienced by persons with epilepsy in Tehran revealed a moderate level of stigma experiences [33]. Another study in Iran reported poor knowledge of epilepsy and that patients with the disease were thought to have compromised mental health [34].…”
Section: Discussionmentioning
confidence: 99%
“…Islam, which is the largest religion worldwide after Christianity, contains some interesting elements on its teachings about persons suffering from different types of disorders. One underlying idea is that whatever happens to a person may be the will of God and not necessarily a punishment for something bad they have done [54]. This suggests that persons suffering from disorders should treat with respect and tolerance.…”
Section: The Effect Of Religion In Improving Stigmamentioning
confidence: 99%
“…Previous studies exploring the experience of discrimination in people with epilepsy have either recruited from a secondary care setting or through epilepsy support groups, which may bias results towards the experience of those with more severe epilepsy or who are finding living with epilepsy the most challenging [11][12][13][14] . In these studies the experience of discrimination was reported in 44% to 56% of people with epilepsy 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…In these studies the experience of discrimination was reported in 44% to 56% of people with epilepsy 12,13 . The few community based studies on this topic also found that up to half of people with epilepsy reported experiences of unfair treatment as a result of their epilepsy 15,16 but did not include a control population.…”
Section: Introductionmentioning
confidence: 99%